2013
DOI: 10.1136/annrheumdis-2012-203130
|View full text |Cite
|
Sign up to set email alerts
|

What is the evidence for the presence of a therapeutic window of opportunity in rheumatoid arthritis? A systematic literature review

Abstract: Even when heterogeneity of patients is taken into account, prolonged symptom duration is associated with radiographic progression and a lower chance on DMARD-free sustained remission. These data may support the presence of a 'window of opportunity'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
134
0
12

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(155 citation statements)
references
References 36 publications
2
134
0
12
Order By: Relevance
“…Evidence supporting this window of opportunity for RA treatment has recently been reviewed, and the conclusion supported the notion of such an opportunity 11 . The timing and duration of this phase were not clearly defined.…”
Section: Rheumatologymentioning
confidence: 86%
See 2 more Smart Citations
“…Evidence supporting this window of opportunity for RA treatment has recently been reviewed, and the conclusion supported the notion of such an opportunity 11 . The timing and duration of this phase were not clearly defined.…”
Section: Rheumatologymentioning
confidence: 86%
“…The first 12 weeks after the onset of symptoms has previously been suggested as a possible time frame, although the definition of symptom onset has been highly variable in many previous studies. The time frame may indeed be longer, as others have suggested 11 . This has led to a proposal for clearer definitions of disease duration in clinical trials, and this published viewpoint presents a clear summary of many of the issues involved in the timing of such a window 12 .…”
Section: Rheumatologymentioning
confidence: 89%
See 1 more Smart Citation
“…A multitude of studies have demonstrated that early intervention improves outcomes, and in particular, treatment during the so-called "window of opportunity," when patients first develop inflammatory arthritis, may halt development of chronic symptoms altogether 1,2 . We have new classification criteria 3 , developed specifically to aid early identification of patients who are likely to need disease-modifying therapy, and a host of new biologic drugs, in particular anti-tumor necrosis factor therapies, that have revolutionized our ability to suppress disease activity 4 .…”
Section: éTude Et Suivi: Rheumatoid Arthritis In the 21st Centurymentioning
confidence: 99%
“…В целом на фоне терапии, которая проводится согласно современным стандартам, стойкая ремиссия достигается у 20-40% пациентов [2,9]. Одним из реша-ющих факторов возможности достижения стойкой ре-миссии является ранее начало терапии, что соответству-ет концепции «окна возможности» (window of opportunity) [26]. У пациентов, получающих ингибиторы фак-тора некроза опухоли α (ФНОα), сочетанное примене-ние МТ являлось предиктором «стойкой» ремиссии, в то время как исходная активность заболевания, ЧПС, возраст, пол, длительность заболевания, функциональ-ная недостаточность плохо коррелировали с последую-щим развитием ремиссии [27].…”
unclassified